2014
DOI: 10.1007/978-3-642-54830-7_18
|View full text |Cite
|
Sign up to set email alerts
|

On Asymmetric Unification and the Combination Problem in Disjoint Theories

Abstract: Abstract. Asymmetric unification is a new paradigm for unification modulo theories that introduces irreducibility constraints on one side of a unification problem. It has important applications in symbolic cryptographic protocol analysis, for which it is often necessary to put irreducibility constraints on portions of a state. However many facets of asymmetric unification that are of particular interest, including its behavior under combinations of disjoint theories, remain poorly understood. In this paper we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Proof. The result follows directly from the proof contained in [7]. There it is shown that Algorithm 3 is both sound and complete.…”
Section: Combining Automata Based Asymmetric Algorithms With the Free...mentioning
confidence: 70%
See 4 more Smart Citations
“…Proof. The result follows directly from the proof contained in [7]. There it is shown that Algorithm 3 is both sound and complete.…”
Section: Combining Automata Based Asymmetric Algorithms With the Free...mentioning
confidence: 70%
“…The problem of asymmetric unification in the combination of disjoint theories was studied in [7] where an algorithm is developed for the problem. However, the algorithm of [7] does not immediately apply to the two methods developed in this paper. This is due to the nature of the two automata based approaches.…”
Section: Combining Automata Based Asymmetric Algorithms With the Freementioning
confidence: 99%
See 3 more Smart Citations